Citrobacter freundii septicemia in a stranded newborn Cuvier's beaked whale (Ziphius cavirostris) - Fernández Rodríguez, Antonio Jesús; Vela, Ana Isabel; Andrada Borzollino, Marisa Ana; Herráez Thomas, Pedro Manuel; Diaz Delgado, Josue; Domínguez, Lucas; Arbelo Hernández, Manuel Antonio (Journal of Wildlife Diseases, 2011)
Citrobacter freundii, a gram-negative enterobacterium, may cause fatal septicemia in humans and animals. Its potential pathogenic role in cetaceans (bottlenose dolphins and beluga whales) has been hypothesized. Here we describe fatal C. freundii septicemia in a stranded newborn Cuvier's beaked whale (Ziphius cavirostris). 1046 1043 0,602 1,079 Q2 Q2 SCIE